Detection of Neuroinflammation in a Rat Model of Subarachnoid Hemorrhage Using [F]DPA-714 PET Imaging - Clément Thomas MD; Johnny Vercouillie PhD; Aurélie Doméné; Clovis Tauber PhD; Michael Kassiou PhD; Denis Guilloteau PhD; Christophe Destrieux MD, PhD; Sophie Sérrière PhD; Sylvie Chalon PhD (Molecular Imaging)
Subarachnoid hemorrhage (SAH) can lead to delayed cerebral ischemia, which increases the rate of morbidity and mortality. The detection of microglial activation may serve as a biomarker for the identification of patients at risk of this deleterious consequence. We assessed this hypothesis in a rat model of SAH in which the exploration of neuroinflammation related to microglial activation was correlated with the degree of bleeding. We used the rat filament model and evaluated (at 48 hours postsurgery) the intensity of neuroinflammation using positron emission tomography (PET) imaging with the 18-kDa translocator protein (TSPO) tracer [ 18 F]DPA-714, quantitative autoradiography with [ 3 H]PK-11195, and SAH grade by postmortem brain picture. High SAH grades were strongly and positively correlated with in vivo PET imaging of TSPO in the cortex and striatum. In addition, a positive correlation was found in the cortex in TSPO, with densities determined by imaging and autoradiographic approaches. Qualitative immunofluorescence studies indicated that overexpression of TSPO was linked to astrocytic/microglial activation. In this model, PET imaging of TSPO using [ 18 F]DPA-714 appeared to be a relevant index of the degree of bleeding, indicating that this imaging method could be used in human patients to improve the management of patients with SAH.